THE ROLE OF ELECTRONIC WORD OF MOUTH ON CONSUMER SATISFACTION AND ITS IMPACT ON REUSING THE GOFOOD FOOD DELIVERY SERVICE APPLICATION IN MEDAN CITY - Muhammad Ferdiananda Chadafi; Nanda Nur Sofyana; Qisthy Rahmah Chairani (Jurnal Ekonomi, 2022)
This study aims to analyse the effect of electronic of mouth on the re-use of GoFood; a food delivery services with satisfaction variable as an intervening variable. The object of this research is GoFood user in Medan city. The sampling technique was carried out using an accidental sampling for 140 respondents, who use GoFood as their food delivery service. The method used is SEM PLS with WarpPLS 7.0 application. The result shows that the electronic word of mouth variable has a positive effect on consumer satisfaction, and the consumers want to re-use. This study also proves that the consumer satisfaction variable is a mediator in an electronic word of mouth and re-use in Gofood in Medan city.